Analisis Faktor-Faktor yang Mempengaruhi Perkembangan Anak Usia 0-2 Tahun - Mustikaati, Wina; Habwah, Alfia; Aulia, Fitri Rohmatul; Putri, Kinanti Dilla; M, Meilisa (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The age period of 0-2 years is known as a crucial period which is often referred to as the golden age or the first 1000 days of life, starting from the time in the womb until the child reaches the age of 2 years (Jesica Hayu, 2023). During this period, children experience very rapid and striking growth and development in various aspects, such as cognitive (intelligence), motoric (gross and fine), language, and socio-emotional (Jesica Hayu, 2023). The achievement of optimal growth and development during this period is greatly influenced by the complex interaction between genetic factors and the bio-physico-psychosocial environment. Based on the existing literature, there are several factors that influence the development of children aged 0-2 years, including internal factors such as genetics, as well as external factors that include prenatal conditions (pregnancy), childbirth factors (complications), and postpartum factors such as nutrition (maternal nutrition during pregnancy and child nutrition), stimulation, environment (family, socio-economic, physical), health status (susceptibility to disease, health care), and parental education (especially the mother). One study showed that nutritional fulfillment is the most significant factor that causes developmental disorders in toddlers aged 1-2 years (Hartini, 2018). This literature study aims to synthesize information from various available sources to analyze key factors that influence child development at age 0-2 years.